2020
DOI: 10.1186/s12866-020-01958-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of the globular heads of the C1q receptor in TcdA-induced human colonic epithelial cell apoptosis via a mitochondria-dependent pathway

Abstract: Background: Clostridioides (formerly Clostridium) difficile infection is the leading cause of antibiotic-associated colitis. Studies have demonstrated that C. difficile toxin A (TcdA) can cause apoptosis of many human cell types. The purpose of this study was to investigate the relationships among exposure to TcdA, the role of the receptor for the globular heads of C1q (gC1qR) gene and the underlying intracellular apoptotic mechanism in human colonic epithelial cells (NCM 460). In this study, gC1qR expression … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Some studies have shown that increased microglia activation results from the release of large amounts of C1q. , Reduced microglia activation in the AD mice model is associated with C1q loss . Following this, we assessed the effect of TW-7 on the activation of microglia by C1q in mice treated with LPS (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that increased microglia activation results from the release of large amounts of C1q. , Reduced microglia activation in the AD mice model is associated with C1q loss . Following this, we assessed the effect of TW-7 on the activation of microglia by C1q in mice treated with LPS (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…TcdA may induce Bak protein production via prostaglandin E2 [136,137]. The death receptor pathway involves caspase 8 activation by the tumor necrosis factor-alpha (TNF-α) or Fas binding, triggering cell death and cytochrome c release from mitochondria [133,138].…”
Section: Cellular Impactsmentioning
confidence: 99%
“…Toxins weaken granule cohesion with the plasma membrane, facilitating degranulation via actin rearrangement. TcdB activates intracellular signaling in mast cells, including p38 MAP, promoting prostaglandin production and degranulation [138,173]. Interestingly, mast cell-deficient mice show reduced inflammatory responses and do not develop TcdA-induced enteritis [153].…”
Section: Interaction Of Tcda and Tcdb With The Host Immune Cellsmentioning
confidence: 99%